The Survival of Mafic Magmatic Enclaves and the Timing of Magma Recharge. Issue 14 (21st July 2020) - Ruprecht, Philipp; Simon, Adam C.; Fiege, Adrian
Abstract: Many intermediate to felsic intrusive and extrusive rocks contain mafic magmatic enclaves that are evidence for magma recharge and mixing. Whether enclaves represent records of prolonged mixing or syn‐eruptive recharge depends on their preservation potential in their intermediate to felsic host magmas. We present a model for enclave consumption where an initial stage of diffusive equilibration loosens the crystal framework in the enclave followed by advective erosion and disaggregation of the loose crystal layer. Using experimental data to constrain the propagation rate of the loosening front leads to enclave "erosion" rates of 10 −5 –10 −8 cm/s for subvolcanic magma systems. These rates suggest that under some circumstances, enclave records are restricted to syn‐eruptive processes, while in most cases, enclave populations represent the recharge history over centuries to millennia. On these timescales, mafic magmatic enclaves may be unique recorders that can be compared to societal and written records of volcano activity. Plain Language Summary: Two major questions in volcano research are how magma chambers are built through time and how they are disrupted to cause volcanic eruptions. One piece of evidence that chambers are assembled by episodic magma addition from below (called "recharge") comes from mingled magmas, where mingling is expressed by the presence of two or more chemically distinct magmas. In particular, the more primitive magma in such mingled magmas is commonly present as discrete blobs, called mafic magmatic enclaves. These enclaves are often interpreted as evidence for recharge‐triggered volcanic eruptions. However, they may also form during recharge episodes that are not associated with volcanic eruptions and instead only feed and sustain the magma chamber. Here, we develop a model that estimates how long mafic magmatic enclaves survive in a chemically distinct magma chamber to better understand how information drawn from enclaves informs the two major questions above. We find that under most common conditions, they survive for centuries to millennia. Therefore, the presence of enclaves is not explicitly evidence for a recharge‐triggered eruption without studying them in greater detail. That detail can then potentially provide information regarding both the run up to eruption as well as magma assembly over centuries and millennia. Key Points: Common survival times for mafic enclaves in felsic volcanic systems are centuries to millennia extending timescale records from minerals Mafic enclaves record only syn‐eruptive processes in hot magmatic systems Mafic enclaves in plutonic systems may represent recharge histories of 10, 000–100, 000 years